SmFeN material and preparation method thereof
By using polymetaphosphate cladding to coat SmFeN material, the problems of easy oxidation of materials and production safety hazards are solved, and the stability and performance of materials are improved.
Patent Information
- Application Number
- CN202311180203.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-13
- Publication Date
- 2025-03-14
AI Technical Summary
SmFeN materials are prone to oxidation during the preparation process, resulting in reduced performance. The existing coating methods will affect the strength and toughness of the material, and there are safety hazards in the production process.
Polymemephosphate is used as the cladding layer to form a positively charged colloid by reacting with calcium ions and ferrous ions in the SmFeN material, and coated on the surface of the SmFeN material to form a dense protective film.
It effectively avoids the oxidation of SmFeN material, improves the stability and safety of the material, and ensures the activity and magnetism of the material, so that its intrinsic coercive force is ≥15.86Koe.
Smart Images

Figure BDA0004446982410000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetic materials and relates to a SmFeN material and a preparation method thereof. Background Art
[0002] SmFeN permanent magnet materials are valued for their excellent magnetic properties and good temperature stability. SmFeN has the advantages of high Curie temperature, good temperature and chemical properties, and low price. As the most valuable permanent magnet material after NdFeB, it is a permanent magnet material that may surpass NdFeB in performance. In terms of physical and chemical properties, SmFeN has higher corrosion resistance, oxidation resistance, and high temperature resistance than NdFeB. It has important application value and broad market prospects in various extreme environmental conditions, especially in the automotive industry, consumer electronics, aerospace and other fields. In addition, in terms of price, samarium and iron raw materials are abundant and cheap, and have a good raw material cost advantage compared to NdFeB.
[0003] Moreover, similar to sintered NdFeB, the particle size of SmFeN magnetic powder has a great influence on its performance. If the powder is too coarse, it will have a serious impact on the coercive force and orientation degree. If the powder is too fine, it will cause severe oxidation, resulting in a significant reduction in magnetic properties and mechanical strength.
[0004] Among the methods for preparing rare earth permanent magnet alloys, the rapid quenching method, powder metallurgy method and hydrogen crushing method have complex processes, long cycles, high energy consumption and difficulty in industrial production. For example, CN 114008728A discloses a samarium iron nitrogen magnetic material, the raw metals are Sm, Fe, Go, Zr, Ti, the samarium iron alloy powder is obtained by melt rapid quenching method, and the SmFeN powder is obtained by heat treatment at 460°C for 8h in a nitrogen atmosphere. The melt rapid quenching method has a complex process, high production cost, and the obtained powder is relatively active and easily oxidized, affecting the performance.
[0005] The powder obtained by high-energy ball milling has a disordered structure. In addition to the SmFeN phase, the powder also contains many impurities. The reduction diffusion method uses metal Ca or CaH 2 , CaCl 2 Calcium compounds such as calcium are mixed with cheap metal oxides or metal chloride raw materials and metal raw materials such as Fe, and heated in high temperature Ar or N 2 In the atmosphere, using metal Ca or CaH 2 The strong reducing property of the metal oxide reacts with the metal oxide to produce the required SmFeN powder. Although the reduction diffusion method obtains less SmFeN impurities, it is subject to the production process. The products obtained are all in block form and contain Ca element compounds and Ca residues. Ball milling is required for crushing. During the ball milling process, the material will release a lot of heat, and the powder is easily oxidized or even burned, which is not conducive to subsequent drying.
[0006] Therefore, if the powder is coated before the drying process to form a dense protective film, not only the performance of the material can be guaranteed, but also the safety of the production process can be guaranteed; for example, CN105702407A discloses a method for preparing a magnetic ceramic coated SmFeN permanent magnet material, which is mixed with ferrous chloride, butyl titanate and other substances, heated in a water bath and concentrated to obtain a ceramic intermediate gel, and then the samarium powder and the iron powder are mixed and smelted, annealed and ball-milled into metal powder, and the bonding metal powder is wrapped with the ceramic intermediate gel with magnetic surface, and composite firing is performed to obtain a magnetic ceramic coated SmFeN permanent magnet material; although its coating can make the material stable and not easy to oxidize, the ceramic coating inevitably reduces the strength, plasticity and toughness of the material, making it difficult to use.
[0007] Based on the above research, it is necessary to provide a SmFeN material, which not only ensures the performance of the powder but also avoids dangers in the production process. Summary of the invention
[0008] The object of the present invention is to provide a SmFeN material and a preparation method thereof. The SmFeN material is coated with a coating layer to improve the stability of the SmFeN material, making it less prone to oxidation. While ensuring the activity and magnetism of the SmFeN material, the safety of the SmFeN material during refinement and drying is effectively improved.
[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a SmFeN material, comprising a core and a coating layer, wherein the core comprises SmFeN, and the coating layer comprises polymetaphosphate.
[0011] Since SmFeN material has poor stability and is easy to oxidize, conventional coating can overcome the problem of easy oxidation, but it will have a great impact on the performance. Therefore, the present invention adopts polymetaphosphate as a coating layer to avoid oxidation of the material, so that the intrinsic coercive force of the SmFeN material is ≥15.86Koe, while ensuring the activity and magnetism of the product. The presence of the coating layer effectively improves the safety of the SmFeN material during refinement and drying.
[0012] Preferably, the coating layer and the raw material for preparing the coating layer both include polymetaphosphate.
[0013] Preferably, the coating layer includes a substance formed by polyacrylate ions, calcium ions and ferrous ions.
[0014] Preferably, the polymetaphosphate used to prepare the coating layer includes any one of sodium polymetaphosphate, potassium polymetaphosphate or lithium polymetaphosphate, or a combination of at least two of them. However, the price of lithium polymetaphosphate is much higher than that of sodium polymetaphosphate and potassium polymetaphosphate. Based on cost considerations, the polymetaphosphate of the present invention is preferably sodium polymetaphosphate and / or potassium polymetaphosphate.
[0015] Preferably, the particle size D50 of the SmFeN material is 0.5-1.5 μm, for example, 0.5 μm, 1.0 μm, 1.25 μm or 1.5 μm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0016] Preferably, the average thickness of the coating layer is 0.1-0.2 μm, for example, 0.1 μm, 0.15 μm or 0.2 μm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0017] In a second aspect, the present invention provides a method for preparing the SmFeN material as described in the first aspect, the preparation method comprising the following steps:
[0018] (1) In a nitrogen-containing atmosphere, a samarium source and an iron source are mixed to obtain a crude SmFeN product;
[0019] (2) The polymetaphosphate, the nitrogen-containing solution and the crude SmFeN product of step (1) are mixed, solid-liquid separated and dried to obtain the SmFeN material.
[0020] The present invention uses a nitrogen-containing solution as a medium, and polymetaphosphate has good solubility in water and is easily hydrolyzed into orthophosphate in warm water or an alkaline solution. Since there are calcium compounds and calcium residues in the crude SmFeN product, which exist in the form of calcium ions in water, polymetaphosphate can react with calcium ions and ferrous ions in water to form a colloid with positive charge, and the colloid particles are deposited toward the cathode to form a film and tightly bonded to the metal surface to form a coating layer, thereby achieving the coating of polymetaphosphate.
[0021] Preferably, the nitrogen-containing atmosphere in step (1) comprises ammonia with a purity of ≥99.9%, for example, 99.9%, 99.95% or 99.99%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0022] Preferably, the mixing method in step (1) comprises jet milling.
[0023] Preferably, the rotation speed of the air flow mill is 100-400 r / min, for example, 100 r / min, 200 r / min, 300 r / min or 400 r / min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0024] Preferably, the samarium source and the iron source in step (1) are both samarium-iron alloys.
[0025] Preferably, the particle size range of the samarium-iron alloy is between 0.1-10 mm, which means that the minimum particle size of the samarium-iron alloy is above 0.1 mm, for example, it can be 0.1 mm, 0.3 mm or 0.5 mm, and the maximum particle size of the samarium-iron alloy is below 10 mm, for example, it can be 10 mm, 9.5 mm or 9 mm, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] The material used in the present invention is a samarium iron alloy prepared by a reduction diffusion method, which is used after being initially crushed by a jaw crusher; since the SmFeN powder before coating is relatively active, if the powder obtained by the air flow mill is fine, the powder is very easy to oxidize, so it is necessary to control the rotation speed of the air flow mill to first obtain SmFeN powder with an average particle size of about 20 μm, and then coat it while crushing to form a dense protective film to reduce the activity of the powder.
[0027] Preferably, the average particle size of the SmFeN crude product in step (1) is 15-25 μm, for example, 15 μm, 20 μm or 25 μm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0028] Preferably, the amount of the polyphosphate added in step (2) is 1-5wt% of the crude SmFeN, for example, 1wt%, 3wt% or 5wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] Preferably, a coating promoting agent is also added during the mixing in step (2).
[0030] Preferably, the addition amount of the coating promoter is 0.5-1wt% of the crude SmFeN, for example, 0.5wt%, 0.7wt%, 0.9wt% or 1wt%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0031] Preferably, the coating-facilitating agent comprises a polyacrylate.
[0032] The polyacrylate of the invention is easily soluble in water, insoluble in organic solvents such as ethanol and acetone, and does not decompose when heated to 300°C. The carboxyl groups on the molecular chains stretch the twisted polymer chains due to electrostatic repulsion, thereby exposing the functional groups with adsorptivity to the surface. Since these active points are adsorbed on the colloidal particles and the metal powder, a bridge between the colloidal particles and the metal powder is formed, thereby accelerating the coating of the colloidal particles. At the same time, the polyacrylate can also be used as a dispersant to disperse the colloid formed by sodium polymetaphosphate, ferrous ions and calcium ions and the metal powder in water without precipitation, thus achieving two goals at one stroke.
[0033] Preferably, the polyacrylate comprises sodium polyacrylate and / or potassium polyacrylate.
[0034] Preferably, the relative molecular mass of the polyacrylate is 1000-5000, for example, 1000, 2000, 3000, 4000 or 5000, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0035] The molecular weight of the polyacrylate of the present invention can play a dispersing role within the above-mentioned specific range.
[0036] Preferably, the mixing method in step (2) includes ball milling mixing.
[0037] Preferably, steel balls are added during the ball milling mixing.
[0038] Preferably, the mass ratio of the steel ball to the SmFeN crude product is 30:(0.1-2), for example, it can be 30:0.1, 30:0.5, 30:1, 30:1.5 or 30:2, but is not limited to the listed values. Other unlisted values within the numerical range are also applicable, preferably 30:(0.5-1).
[0039] Preferably, the frequency of the ball milling mixing is 1-5 Hz, for example, 1 Hz, 2 Hz, 3 Hz, 4 Hz or 5 Hz, and the time is 5-20 h, for example, 5 h, 10 h, 15 h or 20 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] Preferably, during the mixing in step (2), the amount of crude SmFeN used is 100-2000 g, for example, 100 g, 500 g, 800 g, 1000 g, 1500 g or 2000 g, but is not limited to the listed values, and other values not listed within the numerical range are also applicable, preferably 500-1000 g.
[0041] Preferably, the nitrogen-containing solution in step (2) comprises aqueous ammonia.
[0042] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises the following steps:
[0043] (1) In an ammonia atmosphere, jet milling the samarium iron alloy at a speed of 100-400 r / min to obtain a crude SmFeN product;
[0044] (2) ball-milling the polymetaphosphate, ammonia water, polyacrylate and the crude SmFeN product of step (1) at a frequency of 1-5 Hz for 5-20 h, and then performing solid-liquid separation and drying to obtain the SmFeN material;
[0045] The amount of polymetaphosphate added is 1-5wt% of the crude SmFeN product, the amount of polyacrylate added is 0.5-1wt% of the crude SmFeN product, and the mass ratio of steel balls to the crude SmFeN product during ball milling is 30:(0.1-2).
[0046] Compared with the prior art, the present invention has the following beneficial effects:
[0047] The present invention uses polymetaphosphate as a coating layer to avoid oxidation of the SmFeN material, effectively improves the safety of the SmFeN material during refinement and drying, and at the same time ensures product activity and magnetism, so that the intrinsic coercive force of the SmFeN material is ≥15.86Koe. DETAILED DESCRIPTION
[0048] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0049] Example 1
[0050] This embodiment provides a SmFeN material, the SmFeN material comprising a core and a coating layer, the core comprising SmFeN, the coating layer comprising a substance formed by polyacrylate ions, calcium ions, and ferrous ions;
[0051] The preparation method of the SmFeN material comprises the following steps:
[0052] (1) In an ammonia atmosphere with a purity of 99.9%, 2000 g of samarium-iron alloy (the atomic ratio of samarium to iron is 2:17) is jet-milled at a speed of 300 r / min to obtain a crude SmFeN product, wherein the average particle size of the crude SmFeN product is 20 μm;
[0053] (2) 24 g of sodium polymetaphosphate (sodium hexametaphosphate, Na 6 O 18 P 6), ammonia water, 5.6 g of sodium polyacrylate (relative molecular weight is about 1880) and 800 g of the crude SmFeN product of step (1) are ball-milled at a frequency of 3 Hz for 10 h, the steel ball during the ball-milling is 30 kg, the mass ratio of the steel ball to the crude SmFeN product is 30:0.8, the liquid level of the ammonia water is 5 cm higher than the steel ball, and after the ball-milling is completed, water and slurry are separated, and then dried at 75° C. to obtain the SmFeN material;
[0054] The addition amount of the sodium polymetaphosphate is 3wt% of the crude SmFeN product, and the addition amount of the sodium polyacrylate is 0.7wt% of the crude SmFeN product.
[0055] Example 2
[0056] This embodiment provides a SmFeN material, the SmFeN material comprising a core and a coating layer, the core comprising SmFeN, the coating layer comprising a substance formed by polyacrylate ions, calcium ions, and ferrous ions;
[0057] The preparation method of the SmFeN material comprises the following steps:
[0058] (1) In an ammonia atmosphere with a purity of 99.9%, 2000 g of samarium-iron alloy (the atomic ratio of samarium to iron is 2:17) is jet-milled at a speed of 100 r / min to obtain a crude SmFeN product, wherein the average particle size of the crude SmFeN product is 25 μm;
[0059] (2) Potassium polymetaphosphate (sodium hexametaphosphate, Na 6 O 18 P 6 ), ammonia water, potassium polyacrylate (relative molecular weight is about 4000) and 500g of the crude SmFeN product of step (1) are ball-milled at a frequency of 1 Hz for 20 hours, the steel ball during the ball-milling is 30 kg, the mass ratio of the steel ball to the crude SmFeN product is 30:0.5, the liquid level of the ammonia water is 5 cm higher than the steel ball, and after the ball-milling is completed, water and slurry are separated, and then dried at 75° C. to obtain the SmFeN material;
[0060] The amount of potassium polymetaphosphate added is 1wt% of the crude SmFeN product, and the amount of potassium polyacrylate added is 0.5wt% of the crude SmFeN product.
[0061] Example 3
[0062] This embodiment provides a SmFeN material, the SmFeN material comprising a core and a coating layer, the core comprising SmFeN, the coating layer comprising a substance formed by polyacrylate ions, calcium ions, and ferrous ions;
[0063] The preparation method of the SmFeN material comprises the following steps:
[0064] (1) In an ammonia atmosphere with a purity of 99.9%, 2000 g of samarium-iron alloy (the atomic ratio of samarium to iron is 2:17) is jet-milled at a speed of 400 r / min to obtain a crude SmFeN product, wherein the average particle size of the crude SmFeN product is 15 μm;
[0065] (2) Sodium polymetaphosphate (sodium hexametaphosphate, Na 6 O 18 P 6 ), ammonia water, sodium polyacrylate (relative molecular weight is about 1000) and 1000g of the crude SmFeN product of step (1) are ball-milled at a frequency of 5 Hz for 5 hours, the steel ball during the ball-milling is 30 kg, and the mass ratio of the steel ball to the crude SmFeN product is 30:1, the liquid level of the ammonia water is 5 cm higher than the steel ball, and the water and slurry are separated after the ball-milling, and then dried at 75°C to obtain the SmFeN material;
[0066] The addition amount of the sodium polymetaphosphate is 5wt% of the crude SmFeN product, and the addition amount of the sodium polyacrylate is 1wt% of the crude SmFeN product.
[0067] Example 4
[0068] This embodiment provides a SmFeN material. The SmFeN material is the same as that in Embodiment 1 except that in the preparation method thereof, the mass of the SmFeN crude product in step (1) is 400 g, the mass ratio of the steel ball to the SmFeN crude product is 30:0.4, and the obtained SmFeN material is changed accordingly.
[0069] Example 5
[0070] This embodiment provides a SmFeN material. The SmFeN material is the same as that in Embodiment 1 except that in the preparation method thereof, the mass of the SmFeN crude product in step (1) is 1200 g, the mass ratio of the steel ball to the SmFeN crude product is 30:1.2, and the obtained SmFeN material is changed accordingly.
[0071] Example 6
[0072] This embodiment provides a SmFeN material, which is the same as that of Embodiment 1 except that in the preparation method of the SmFeN material, the rotation speed of the air flow mill in step (1) is 80 r / min, so that the average particle size of the obtained SmFeN crude product and the SmFeN material change accordingly.
[0073] Example 7
[0074] This embodiment provides a SmFeN material, which is the same as that of Embodiment 1 except that in the preparation method of the SmFeN material, the rotation speed of the air flow mill in step (1) is 600 r / min, so that the average particle size of the obtained SmFeN crude product and the SmFeN material change accordingly.
[0075] Example 8
[0076] This embodiment provides a SmFeN material. The SmFeN material is the same as that in Embodiment 1 except that in the preparation method thereof, the mass of the sodium polymetaphosphate in step (2) is 5 g, and the amount of sodium polymetaphosphate added is 0.625 wt % of the crude SmFeN product, so that the obtained SmFeN material changes accordingly.
[0077] Example 9
[0078] This embodiment provides a SmFeN material. The SmFeN material is the same as that in Embodiment 1 except that in the preparation method thereof, the mass of the sodium polymetaphosphate in step (2) is 50 g, and the amount of the sodium polymetaphosphate added is 6.25 wt % of the crude SmFeN product, so that the obtained SmFeN material changes accordingly.
[0079] Example 10
[0080] This embodiment provides a SmFeN material. The SmFeN material is the same as that in Embodiment 1 except that in the preparation method thereof, the mass of the sodium polyacrylate in step (2) is 2 g, and the amount of the sodium polyacrylate added is 0.25 wt % of the crude SmFeN product, so that the obtained SmFeN material changes accordingly.
[0081] Embodiment 11
[0082] This embodiment provides a SmFeN material. The SmFeN material is the same as that in Embodiment 1 except that in the preparation method thereof, the mass of the sodium polyacrylate in step (2) is 10 g, and the amount of the sodium polyacrylate added is 1.25 wt % of the crude SmFeN product, so that the obtained SmFeN material changes accordingly.
[0083] Example 12
[0084] This embodiment provides a SmFeN material, which is the same as that of Embodiment 1 except that in the preparation method of the SmFeN material, the frequency of the ball milling mixing in step (2) is 0.5 Hz, so that the obtained SmFeN material changes accordingly.
[0085] Embodiment 13
[0086] This embodiment provides a SmFeN material, which is the same as that of Embodiment 1 except that in the preparation method of the SmFeN material, the frequency of the ball milling mixing in step (2) is 7 Hz, so that the obtained SmFeN material changes accordingly.
[0087] Embodiment 14
[0088] This embodiment provides a SmFeN material, which is the same as that of Embodiment 1 except that in the preparation method of the SmFeN material, the ball milling mixing time in step (2) is changed to 3 hours, so that the obtained SmFeN material is changed accordingly.
[0089] Embodiment 15
[0090] This embodiment provides a SmFeN material, which is the same as that of Embodiment 1 except that in the preparation method of the SmFeN material, the ball milling mixing time in step (2) is changed to 25 hours, so that the obtained SmFeN material is changed accordingly.
[0091] Example 16
[0092] This embodiment provides a SmFeN material, which is the same as that of Embodiment 1 except that in the preparation method thereof, sodium polyacrylate is not added in step (2), so that the obtained SmFeN material changes accordingly.
[0093] Comparative Example 1
[0094] This comparative example provides a SmFeN material, which is the same as Example 1 except that in the preparation method of the SmFeN material, sodium polymetaphosphate is not added in step (2), so that the obtained SmFeN material changes accordingly.
[0095] The SmFeN materials obtained in the above examples and comparative examples were tested for oxygen content, nitrogen content, D50, SEM electron microscopy and intrinsic coercivity. The test results are shown in the following table:
[0096] Table 1
[0097]
[0098] From the above table we can see that:
[0099] (1) The SmFeN material powder obtained by the present invention has a low degree of oxidation, and no explosion occurs during the preparation process. The oxygen content of the SmFeN material is in the range of 1.4-3wt%, the nitrogen content is in the range of 2.9-3.2wt%, the particle size D50 is in the range of 0.5-1.5μm, the average thickness of the coating layer is in the range of 0.1-0.21μm, and the intrinsic coercive force is ≥10Koe. This shows that the preparation method of the present invention ensures the activity and magnetism of the product, and the coating of polymetaphosphate effectively improves the safety.
[0100] (2) It can be seen from Example 1 and Examples 4-5 that, when the mass of the steel ball is constant, the mass of the SmFeN crude product added during ball milling will affect the powder particle size. The particle size of the SmFeN powder has a greater influence on the magnetic properties. The larger the powder particle size, the lower the magnetic properties, and the smaller the powder particle size, the higher the magnetic properties. However, a small powder particle size will cause the powder to be easily oxidized, thereby reducing the performance.
[0101] (3) It can be seen from Examples 1 and 6-7 that when the mass of the steel ball and the mass of the powder during ball milling are constant, the rotation speed of the air flow mill will affect the initial particle size of the powder before ball milling and thus affect the magnetic properties. In addition, the rotation speed will affect the nitridation efficiency of the samarium iron alloy during ammonia air flow milling and affect the nitrogen content of the final SmFeN material.
[0102] (4) It can be seen from Example 1 and Examples 8-9 that the addition of sodium polyphosphate during ball milling will affect the powder particle size. If the amount of sodium polyphosphate is insufficient, the average thickness of the coating film will be lower than the normal level, making the powder easily oxidized and resulting in reduced performance. Excessive sodium polyphosphate will cause the powder particle size to become larger, thereby resulting in reduced performance.
[0103] (5) It can be seen from Example 1 and Examples 10-11 that the addition of sodium polyacrylate during ball milling will also affect the powder particle size. Excessive sodium polyacrylate will cause the powder particle size to become larger, thereby resulting in reduced performance. Sodium polyacrylate promotes the coating of sodium polymetaphosphate. Insufficient sodium polyacrylate will result in poor powder coating effect and easy oxidation, resulting in reduced performance.
[0104] (6) It can be seen from Examples 1 and 12-13 that, when the air mill speed, steel ball mass, powder mass and added additives are constant, the ball milling frequency will also affect the powder particle size, ultimately leading to changes in powder properties.
[0105] (7) It can be seen from Example 1 and Examples 14-15 that, when the air mill speed, ball milling frequency, steel ball mass, powder mass and added additives are constant, the ball milling time will also affect the powder particle size, ultimately leading to changes in powder properties.
[0106] (8) It can be seen from Examples 1 and 16 that sodium polyacrylate promotes the coating of sodium polymetaphosphate, and can better coat sodium polymetaphosphate on the surface of SmFeN powder, reduce its activity, reduce oxidation, and improve magnetic properties.
[0107] (9) It can be seen from Example 1 and Comparative Example 1 that sodium polymetaphosphate can coat SmFeN powder to reduce its activity, reduce oxidation, and improve magnetic properties.
[0108] In summary, the present invention provides a SmFeN material and a preparation method thereof. The SmFeN material is coated with a coating layer to improve the stability of the SmFeN material, making it less prone to oxidation. While ensuring the activity and magnetism of the SmFeN material, the safety of the SmFeN material during refinement and drying is effectively improved.
[0109] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A SmFeN material, characterized in that: The SmFeN material comprises a core and a coating layer, wherein the core comprises SmFeN and the coating layer comprises polymetaphosphate.
2. The SmFeN material according to claim 1, characterized in that: The coating layer and the raw materials for preparing the coating layer both include polymetaphosphate; Preferably, the coating layer comprises a substance formed by polyacrylate ions, calcium ions and ferrous ions; Preferably, the polymetaphosphate used to prepare the coating layer includes sodium polymetaphosphate and / or potassium polymetaphosphate; Preferably, the particle size D50 of the SmFeN material is 0.5-1.5 μm; Preferably, the coating layer has an average thickness of 0.1-0.2 μm.
3. A method for preparing the SmFeN material as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) In a nitrogen-containing atmosphere, a samarium source and an iron source are mixed to obtain a crude SmFeN product; (2) The polymetaphosphate, the nitrogen-containing solution and the crude SmFeN product of step (1) are mixed, solid-liquid separated and dried to obtain the SmFeN material.
4. The preparation method according to claim 3, characterized in that: The nitrogen-containing atmosphere in step (1) comprises ammonia gas with a purity of ≥99.9%; Preferably, the mixing method in step (1) comprises jet milling; Preferably, the rotation speed of the air flow mill is 100-400 r / min.
5. The preparation method according to claim 3 or 4, characterized in that: The samarium source and the iron source in step (1) are both samarium-iron alloys; Preferably, the average particle size of the SmFeN crude product in step (1) is 15-25 μm.
6. The preparation method according to any one of claims 3 to 5, characterized in that: The amount of the polymetaphosphate added in step (2) is 1-5wt% of the crude SmFeN product; Preferably, a coating promoting agent is also added during the mixing in step (2); Preferably, the amount of the coating promoting agent added is 0.5-1wt% of the crude SmFeN; Preferably, the encapsulation promoting agent comprises a polyacrylate; Preferably, the polyacrylate comprises sodium polyacrylate and / or potassium polyacrylate.
7. The preparation method according to any one of claims 3 to 6, characterized in that: The mixing method in step (2) includes ball milling mixing; Preferably, steel balls are added during the ball milling mixing.
8. The preparation method according to claim 7, characterized in that: The mass ratio of the steel ball to the SmFeN crude product is 30:(0.1-2), preferably 30:(0.5-1); Preferably, the frequency of the ball milling mixing is 1-5 Hz, and the time is 5-20 h.
9. The preparation method according to any one of claims 3 to 8, characterized in that: During the mixing in step (2), the amount of crude SmFeN used is 100-2000 g, preferably 500-1000 g; Preferably, the nitrogen-containing solution in step (2) comprises aqueous ammonia.
10. The preparation method according to any one of claims 3 to 9, characterized in that: The preparation method comprises the following steps: (1) In an ammonia atmosphere, jet milling the samarium iron alloy at a speed of 100-400 r / min to obtain a crude SmFeN product; (2) ball-milling the polymetaphosphate, ammonia water, polyacrylate and the crude SmFeN product of step (1) at a frequency of 1-5 Hz for 5-20 h, and then performing solid-liquid separation and drying to obtain the SmFeN material; The amount of polymetaphosphate added is 1-5wt% of the crude SmFeN product, the amount of polyacrylate added is 0.5-1wt% of the crude SmFeN product, and the mass ratio of steel balls to the crude SmFeN product during ball milling is 30:(0.1-2).
Citation Information
Patent Citations
Preparation method of magnetic ceramic-coated SmFeN permanent magnet material
CN105702407A
Samarium-iron-nitrogen-based magnetic material
CN114008728A